PERANAN BUDAYA HUKUM DALAM PERSPEKTIF PEMBANGUNAN HUKUM NASIONAL - Marzuki Lubis (Universitas Medan Area, 2014)
Law as a tool of social engineering so to look at that interdepenced between system of lawwith social culture showed that to build the development of culture of law is a urgentcomponent because will be influence to development substance of law and practice of law